2021
DOI: 10.2144/fsoa-2021-0032
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pelvic Actinomycosis Affecting genital, Urinary and Digestive Tracts: a Rare Misleading Diagnosis

Abstract: Pelvic actinomycosis is an uncommon chronic invasive disease caused by a bacteria of the Actinomyces spp. Its diagnosis constitutes a clinical challenge and is usually reached in the postoperative period after resecting a pelvic mass that usually mimics advanced ovarian cancer. Although pelvic actinomyocosis involving the digestive and genital tract has been commonly described, very few reports have described cases involving both ovaries and requiring partial cystectomy for bladder involvement. Herein, we illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…14,15 It has been reported that the rate of preoperative diagnosis is less than 10% and most were diagnosed posteriorly on the anatomopathological examination surgical specimen obtained after the performance of a laparotomy or a laparoscopy to evaluate the suspicious pelvic mass. 7,16 Despite the lack of diagnostic specificity, the role of the CT scan remains essential to evoke the diagnosis of pelvic actinomycosis, to specify its extent and its impact on the neighboring organs, and to evaluate the effectiveness of the treatment. CT scan results of an infiltrating abdominopelvic mass without border limits and increased heterogeneous contrast may suggest actinomycosis, especially in patients with fever, leukocytosis, or predisposing factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 It has been reported that the rate of preoperative diagnosis is less than 10% and most were diagnosed posteriorly on the anatomopathological examination surgical specimen obtained after the performance of a laparotomy or a laparoscopy to evaluate the suspicious pelvic mass. 7,16 Despite the lack of diagnostic specificity, the role of the CT scan remains essential to evoke the diagnosis of pelvic actinomycosis, to specify its extent and its impact on the neighboring organs, and to evaluate the effectiveness of the treatment. CT scan results of an infiltrating abdominopelvic mass without border limits and increased heterogeneous contrast may suggest actinomycosis, especially in patients with fever, leukocytosis, or predisposing factors.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 It has been reported that the rate of preoperative diagnosis is less than 10% and most were diagnosed posteriorly on the anatomopathological examination surgical specimen obtained after the performance of a laparotomy or a laparoscopy to evaluate the suspicious pelvic mass. 7 , 16 …”
Section: Discussionmentioning
confidence: 99%